Factors Influencing Class Rules in Improving Early Childhood Discipline in Siloam Christian Kindergarten Kota Baru Kupang - Oktavianus Armin; Kristin Margiani; Theodorina N. Seran (Universitas Nusa Cendana, 2024)
This study aims to determine what are the factors that influence the classroom rules applied in improving early childhood discipline in Siloam Christian Kindergarten Kota Baru, Kupang City. The method used is descriptive qualitative. The research subjects used were two-person class teachers at Siloam Christian Kindergarten in Kota Baru. Data collection techniques use interview and observation techniques. The results showed that the factors that influence classroom rules are teachers and parents. Teacher and parent factors can be both supporting and inhibiting factors. The teacher's factor in favor of classroom rules is the teacher's knowledge and consistency. The inhibiting factor of being a teacher is teacher delay. The parental factor in supporting the implementation of class rules is applying rules at home. Meanwhile, the parental factor that hinders class rules is inconsistency in applying home rules. Class rules at Siloam Christian Kindergarten Kota Baru Kupang City are well implemented and able to improve early childhood discipline, in implementing classroom rules to improve children's discipline through habituation methods using image media pasted on the classroom wall.